On growth habits and forms: the utility of stem anatomy to define growth habits of Melastomataceae - Naranjo Vásquez, Juan Pablo; Torres, Mauricio; Quijano, Mario Alberto (Instituto de Ecología, A.C., 2018)
Background and Aims: The growth habit is a character commonly used in taxonomic descriptions of plants and one of the first to be taught to students of plant morphology. Defining growth habits has turned into a complex matter due to the proliferation of terms. By definition, some habits can be distinguished by plant stem anatomy, but there are actually few studies that evaluate this correspondence. The family Melastomataceae is an excellent group to investigate how stem anatomy varies among plants with contrasting growth habits because it shows considerable variation in growth habits and stem anatomy. In this study, we analyzed whether stem anatomy characteristics vary consistently across growth habits in species of Melastomataceae.Methods: Eighteen species of Melastomataceae were collected in different Colombian ecosystems. Observation of 125 stem anatomy characters was performed on fixed internode slices, which were cut by freehand in transverse, radial longitudinal, and tangential planes. We used as a prior a classification of growth habits that we consolidated from a literature review, aiming to reconcile multiple schemes of classification of habits across vascular plants.Key results: Few anatomical characteristics were shared exclusively by species of one particular growth habit. Therefore, the Melastomataceae species analyzed here could be grouped in three general growth habits: trees/shrubs, herbaceous, and climbers.Conclusions: Many of the current definitions of growth habits are a mixture of different topics including ecology, specimen size, and the presence of specialized organs. For the concept of growth habits to be useful, it should be avoided to elevate ranges of size, habitats, or specific functional morphology adaptations to the generalized category of growth habits.